Cuban Patriotic emigration from Jamaica during the Ten Years War (Islas, 2025)
Introduction: This article addresses the treatment of Cuban patriotic emigration from Jamaica within the historiography of the independence wars—an aspect that has so far been scarcely explored and, predominantly, addressed in a fragmented manner.Methods: The research was based on the cross-referencing and systematization of information derived from documentary analysis of primary sources and the historiographical production that examines the role of Cuban emigrations in the struggles for independence.Results: The main result lies in the unveiling of the features that characterized the social composition, socioeconomic and cultural life, as well as the political activity of this emigrant community during the period of the Ten Years' War.Conclusions: Despite its heterogeneous social composition and economic limitations, the Cuban emigration from Jamaica acted in favor of the independence struggle and contributed to strengthening the distinctive codes of Cuban nationality.
Keywords: Cuban national history; Cuban patriotic emigration; patriotic emigration to Jamaica; Ten Years' War; History of Cuba